Kemeny revisited: the new homeownership-welfare dynamics. Issue 2 (7th February 2019) - Nethercote, Megan
Abstract: This article connects homeowner subjectivities and state practice to specify how the post-war homeownership-welfare dynamic has radically transformed since the 1980s. Specifically, this article revisits, 35 years on and against the onset of financialized capitalism, Jim Kemeny's seminal thesis on the relationship between homeownership and welfare. Focusing on Australia, as a less considered case in the liberal Anglophone cluster, it traces how the state actively overhauled the local post-war homeownership-welfare dynamic from the late 1970s. The analysis establishes how this refurbishment outdates Kemeny's thesis by rendering features of the post-war homeownership model ineffective and, more significantly, by fashioning new homeowner subjectivities—namely, the investor subject. By bringing together Foucauldian perspectives (mortgage biopolitics) with Marxian political economy, this state-sensitive account both responds to Kemeny's unexpected silence on the active hand of the Australian state in structuring its homeownership-welfare dynamic, and contributes to the asset-based welfare critique by emphasizing its post-1980s features and the structural drivers that explain its persistence, despite its unequal wealth and welfare outcomes.